Modelo de avaliação da sustentabilidade corporativa à luz da racionalidade substantiva - Gorniak, Eliziane (2014)
This work considers the sustainability in the context of managing companies operating in Brazil. It focuses on Brazilian companies recognized by a national magazine that publishes an annual Sustainability Guide, aiming to develop theoretical and practical models for the assessment of corporate sustainability through the substantive rationality concept. The data analysis considered the instrumental and substantive rationality typologies. From these typologies, it was possible to analyze the reasons that made the companies adopt sustainability practices. Instrumental rationality consists in the ability to create the means to reach certain ends. Substantive rationality, on the other hand, involves the ability to morally, ethically and politically judge both means and ends. The target was 21 companies nominated by the Sustainability Guide as the models in sustainability in Brazil in 2011. The collected data were bibliographic, documentary and based on field research questions developed specifically for this research. The main sources were the Sustainability Guide and GRI - Global Sustainability Reports. The results showed that the predominant rationality model in 59% of the companies analyzed is the instrumental one. In other words, the decision making process is motivated by the opportunity to maximize the productivity and the company returns. The data supported the elaboration of evaluation models based on two dimensions: the analysis of the relevance on the sustainability initiatives with the constituent elements of the substantive rationality and the analysis of the justifications to the realizations of such initiatives. Through this analysis and the elaboration of this model, it is possible to conclude that the analyzed companies are improving and institutionalizing tools to work with self-reflection and awareness of their impacts in society.